Chitosan as a paradigm for biopolymer electrolytes in solid-state dye-sensitised solar cells - Rahman, Noriah Abdul; Hanifah, Sharina Abu; Mobarak, Nadhratun Naiim; Ahmad, Azizan; Ludin, Norasikin Ahmad; Bella, Federico; Su'ait, Mohd Sukor (Polymer (Guilford), 2021)
Biopolymers are among the most promising electrolyte hosts for different electrochemical devices in the energy conversion and storage fields. In this work, the potential of chitosan as a biopolymer laden with NaI salt is explored and applied as solid polymer electrolyte for dye sensitised solar cells. The chitosan-NaI electrolyte is successfully prepared via a simple and upscalable solution casting technique. Infrared spectroscopy analysis highlights interactions between chitosan and NaI, that weaken the semi-crystalline domains of chitosan and favour the conduction of the redox shuttle ions between cell electrodes. At room temperature, the best ionic conductivity was obtained for the samples laden with NaI 30 wt%, with values equal to 1.11 × 10−4 S cm−1. Na+ transference number determination indicates that only 0.9% of the ionic conductivity is determined by these cations, thus highlighting that I− anions represent the active species in the newly proposed solid-state electrolyte. This result is highly desired considering that these anions are those responsible for the regeneration of oxidized dye molecules in the cell and, overall, for the cell efficiency. Current-voltage measurement of solid-state photovoltaic devices under simulated sunlight led to a reproducible and stable power conversion efficiency of 0.06%, along with a short-circuit current density of 0.32 mA cm−2, an open circuit voltage of 0.7 V and a fill factor 0.3. [Display omitted] •A chitosan-based solid-state systems is proposed for stable and sustainable solar cells.•A careful electrochemical and structural investigation is proposed to define the features of proposed system.•The redox shuttle transference number is optimized to maximize dye molecules regeneration.•A preliminary efficiency for a 100% solid-state and biosourced hybrid photovoltaic systems in achieved.